Penyelundupan dan Human Trafficking di Perbatasan Maritim Indonesia di Wilayah Nusa Tenggara Timur dan Kalimantan Utara - Sampetoding, Catherind Zefanya; Burhanuddin, Agussalim (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study explores the phenomena of smuggling and human trafficking across Indonesia’s maritime borders, particularly in the regions of East Nusa Tenggara and North Kalimantan. These areas are considered vulnerable due to weak border surveillance, high levels of undocumented migration, and the presence of transnational networks. The research highlights structural factors, such as socio-economic conditions and limited institutional capacity, which contribute to the persistence of these illicit activities. Using a qualitative approach and field data, the study underscores the importance of cross-sector collaboration and improved surveillance capacity to comprehensively address these issues.